HUBUNGAN ANTARA DAYA LEDAK OTOT BAHU DAN KEKUATAN GENGGAMAN TERHADAP KEMAMPUAN TOLAK PELURU GAYA MENYAMPING PADA SISWA PUTRA MTs NW KORLEKO - Pahmi, Izmul; Jamaludin, Jamaludin; Subakti, Subakti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2019)
The explosive force of the shoulder muscles and the strength of the grasp is a contributing factor in the ability of sideways force to decline in determining the repulsion of an athlete. Problems in this research are Lack of ability to sideways to turn sideways force on student of MTs NW korleko Lesson year 2016-2017. The formulation of the problem in this research is whether there is a correlation between the explosive force of the shoulder muscles and the strength of the grip on the ability of sideways styles tossing force on students of MTs MTs NW Korleko academic year 2016-2017 ". This study aims to determine the relationship between the explosive force of the shoulder muscles and the strength of the grip on the ability of sideways styles tossing force on students of MTs NW korleko academic year 2016-2017 ". Rancagan research used in this study using Pearson product moment correlation. The type of research used is descriptive qualitative correlation. Population in this research is student of student of MTs NW Korleko year 2016-2017 which amount to 18 people. Data collection techniques use action and documentation tests. Data analysis techniques use multiple linear correlation statistics. From result of analysis of double correlation (R) obtained value = 0,541 bigger than r table value with significant level 5% that is 0,468. Then it can be concluded that there is a significant relationship between the explosive force of the shoulder muscles and the strength of the grip on the ability of sideways styles tossing force on students of MTs NW korleko. Â 